The Chytrid Fungus Batrachochytrium dendrobatidis Infecting the Creole Frog, Leptodactylus latrans, in a New Region of West Argentina - Ghirardi, Romina (2018)
We analyzed Bd infection in six specimens of L. latrans deposited in the herpetological collection of Instituto y Museo de Ciencias Naturales from Universidad Nacional de San Juan. Histological examination revealed presence of Bd in all six studied specimens. Our results add a new record of Bd to the list of L. latrans infected and in a new bioregion from Argentina. Moreover, the apparently widespread infection of this chytrid fungus in populations of L. latrans from different climates, elevations, and bioregions, without a single report of population declines ascribable to Bd, suggests that L. latrans may act as a reservoir host. Further screening for chytridiomycosis is required, as well as population monitoring, especially in L. latrans populations and in other species that are sympatric with L. latrans across its broad distribution.